Traumatic Enthesophyte From a Chronic Pectoralis Major Tendon Rupture: A Case Report. Issue 3 (July 2021) - Nadig, Nischal; Jaber, Jamil; Cameron, Craig; Antosh, Ivan
Abstract : Case: A 24-year-old active duty soldier with a chronic pectoralis major tendon rupture presented a year later with a bony lesion consistent with an enthesophyte at the humeral insertion. The patient continued to have pain that was affecting his activities of daily living and underwent surgical intervention. Conclusion: Operative management with enthesophyte excision and pectoralis major tendon repair provided relief to the patient's symptoms and return to preinjury levels of function as evaluated with Tegner, single assessment numeric evaluation, and visual analog scale scores at the 2-year follow-up.